The energy payback time of advanced crystalline silicon PV modules in 2020: a prospective study. (11th February 2013) - Mann, Sander A.; de Wild‐Scholten, Mariska J.; Fthenakis, Vasilis M.; van Sark, Wilfried G.J.H.M.; Sinke, Wim C.
ABSTRACT The photovoltaic (PV) market is experiencing vigorous growth, whereas prices are dropping rapidly. This growth has in large part been possible through public support, deserved for its promise to produce electricity at a low cost to the environment. It is therefore important to monitor and minimize environmental impacts associated with PV technologies. In this work, we forecast the environmental performance of crystalline silicon technologies in 2020, the year in which electricity from PV is anticipated to be competitive with wholesale electricity costs all across Europe. Our forecasts are based on technological scenario development and a prospective life cycle assessment with a thorough uncertainty and sensitivity analysis. We estimate that the energy payback time at an in‐plane irradiation of 1700 kWh/(m2 year) of crystalline silicon modules can be reduced to below 0.5 years by 2020, which is less than half of the current energy payback time. Copyright © 2013 John Wiley & Sons, Ltd.